MENIMBANG GAGASAN EPISTEMOLOGI ISLAM AL-JABIRI SEBAGAI SOLUSI KEBANGKITAN ISLAM MODERN - Bahrur Rozi, Achmad (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
This article will specifically examine Abid al-Jabiri’s renewal thoughts. The unique and important side of al- Jabiri’s thinking lies in the epistemological criticism carried out on the scientific building that developed in the middle of the Arab-Islamic civilization. Epistemological criticism becomes a realm of science that is not muchnoticed by Muslim thinkers in particular. Moreover, epistemology as part of philosophy has long been kept away from the scientific civilization of the Islamic world; studying philosophy is tantamount to plunging into the abyss of disbelief. At least, the epistemological criticism of al-Jabiri, offers the Islamic world an attempt to reconstruct a building of knowledge of reason to catch up, change the Islamic world towards the progress of civilization, and achieve modernity.Key words: Abid Al-Jabiri, Islamic Epistemolgy, Modernity